1983
DOI: 10.1210/endo-112-2-543
|View full text |Cite
|
Sign up to set email alerts
|

Primary Culture of Purified Leydig Cells Isolated from Adult Rat Testes*

Abstract: Methods for isolating highly purified Leydig cells permit the study of acute responses and biochemical properties of Leydig cells independent of other testicular cell types. The present study describes the development of a primary culture system for purified Leydig cells from adult rats in which the cells retain their ability to secrete testosterone for at least 72 h in culture. When Leydig cells were cultured in tissue culture medium 199--0.1% BSA (M199-BSA), basal testosterone secretion declined by 72 h, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…This contention is supported by the demonstration of high affinity specific insulin binding sites on testicular membrane preparation (Posner et al, 1974;Saucier et al, 1981;Abele et al, 1986). Indeed, previous studies have shown that addition of insulin to cultured rat interstitial cells (Adashi et al, 1982) or to purified rat Leydig cells (Browning et al, 1983;Abele et al, 1985a) enhanced the hCG-induced testosterone production. However, since the conentrations used in these studies were high (0.1 to 10 pg/ml), the possibility exists that the effect of insulin may reflect the consequence of its action through the Sm-C receptor.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This contention is supported by the demonstration of high affinity specific insulin binding sites on testicular membrane preparation (Posner et al, 1974;Saucier et al, 1981;Abele et al, 1986). Indeed, previous studies have shown that addition of insulin to cultured rat interstitial cells (Adashi et al, 1982) or to purified rat Leydig cells (Browning et al, 1983;Abele et al, 1985a) enhanced the hCG-induced testosterone production. However, since the conentrations used in these studies were high (0.1 to 10 pg/ml), the possibility exists that the effect of insulin may reflect the consequence of its action through the Sm-C receptor.…”
Section: Discussionmentioning
confidence: 96%
“…The original rationale for this investigation was the previous in vitro demonstrations of effects of insulin at high concentrations in several cell models (Froesch et al, 1985) including rat Leydig cells (Adash et al, 1982;Browning et al, 1983;Abele et al, 1985). Our results indicated that Sm-C at nanomolar concentrations stimulated Leydig cell DNA synthesis and cell mutiplication while micromolar concentrations of insulin were required to obtain the same effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leydig cells in primary culture have been used to study the mechanism of action of gonadotropin, but testosterone production is not sustained more than a few days (2)(3)(4)(5)(6). Clonal cell lines derived from mouse (7)(8)(9) and rat (10) Leydig cell tumors, although they may retain LH/hCG receptors, are unable to pursue steroidogenesis beyond progesterone synthesis.…”
Section: For Review)mentioning
confidence: 99%
“…Density gradient centrifugation has been reported as the classical method for harvesting LCs. [18][19][20][21][22][23] However, the cell number of harvested LCs in this method was very limited with complicated procedures and the obtained cells showed very poor proliferative potential in vitro. 24 Therefore, it is urgent and necessary to establish a modified harvesting and expanding system for obtaining adequate LCs.…”
Section: Introductionmentioning
confidence: 99%